Long-term corticosterone exposure decreases insulin sensitivity and induces depressive-like behaviour in the C57BL/6NCrl mouse. - Eva L van Donkelaar (PLoS ONE, 2014)
Chronic stress or long-term administration of glucocorticoids disrupts the hypothalamus-pituitary-adrenal system leading to continuous high levels of glucocorticoids and insulin resistance (IR). This pre-diabetic state can eventually develop into type 2 diabetes mellitus and has been associated with a higher risk to develop depressive disorders. The mechanisms underlying the link between chronic stress, IR and depression remains unclear. The present study aimed to establish a stress-depression model in mice to further study the effects of stress-induced changes upon insulin sensitivity and behavioural consequences. A pilot study was conducted to establish the optimal administration route and a pragmatic measurement of IR. Subsequently, 6-month-old C57BL/6NCrl mice were exposed to long-term oral corticosterone treatment via the drinking water. To evaluate insulin sensitivity changes, blood glucose and plasma insulin levels were measured at different time-points throughout treatment and mice were behaviourally assessed in the elevated zero maze (EZM), forced swimming test (FST) and open field test to reveal behavioural changes. Long-term corticosterone treatment increased body weight and decreased insulin sensitivity. The latter was revealed by a higher IR index and increased insulin in the plasma, whereas blood glucose levels remained unchanged. Corticosterone treatment induced longer immobility times in the FST, reflecting depressive-like behaviour. No effects were observed upon anxiety as measured in the EZM. The effect of the higher body weight of the CORT treated animals at time of testing did not influence behaviour in the EZM or FST, as no differences were found in general locomotor activity. Long-term corticosterone treatment via the drinking water reduces insulin sensitivity and induces depressive-like behaviour in the C57BL/6 mouse. This mouse model could thus be used to further explore the underlying mechanisms of chronic stress-induced T2DM and its association with increased prevalence of major depressive disorder on the short-term and other behavioural adaptations on the longer term.